Using foresight practice to imagine the future(s) of mutual aid - Annie Zean Dunbar; Danielle Maude Littman; Madi Boyett; Kimberly Bender; Kate Saavedra; Colleen Cummings Melton; Tara Milligan; Colin Bogle (Social Work and Society)
Most social work research explores ways to prevent or ameliorate social problems to relieve human suffering. Less common in social work is research which considers the future as a preparative tool to address challenges faced today. This qualitative methods paper describes the uses of a foresight lens and futures-focused framework to analyze empirical research. The paper first provides insight into speculative turns toward futures practice within academic and non-academic traditions in the United States. It describes the ways foresight has emerged within social work research and beyond. Next, the paper contextualizes the case study of mutual aid as a community strategy and research focus within a U.S. context. Then, the paper provides the steps the research team took to use Dator's (2009) four futures framework, which analyzed interviews of mutual aid participants and organizers (N=25) during the early months of the COVID-19 pandemic. The research team provides insights and best practices for using the foresight lens as an analytical tool, including reflexivity, flexibility, and an emphasis on centering participant voices. The paper ends with limitations and implications for the use of foresight practice and future-focus tools in the field of social work as a means to help prepare researchers, practitioners, and educators for the complex crises yet to come.